Resilienzauktionen für Nullemissionstechnologien - André Wolf (Wirtschaftsdienst, 2024)
Europe's rapid transition to a low-carbon economy has put a limited number of renewable energy technologies, such as heat pumps and solar panels, at the centre of the EU's industrial strategy. For some of these net-zero technology goods, the EU has significant import dependencies on a few third countries, notably China. This exposes European supply chains to risks that are difficult to manage. In response, the EU has set the stage for a new market-based instrument: the introduction of resilience criteria in public procurement and renewable energy support auctions. This article discusses the rationale for such criteria and examines the strengths and weaknesses of different design options. Using the example of support auctions for ground-mounted PV in Germany, it simulates the impact of a resilience bonus on support costs and demand for domestic PV modules.
Keywords: F13; L41; Q58; 330